Artificial Intelligence (AI) Website Developer: Aesthetic Convenience For Web Designers And Graphic Designers Without Coding - Azhari Amri (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
Not only Chat GPT, the development of web design programs today, there are many ways to consider visual aspects as a method to facilitate the capture and browsing of information. I conclude this term from my experience when creating digital information on website platforms. Graphic design or visual communication design is also challenged to continue collaborating with many fields of study, one of which is information technology (IT) and programmers. A programmer or website developer needs a visual touch to facilitate user attractiveness in reviewing the application or program. Likewise with a graphic designer, the ability to do layout, composition, illustration and text is arranged to facilitate users and speed up the performance of the program. One of the most interesting principles in designing is Aesthetics. Aesthetics is a branch of philosophy that deals with the nature of beauty, art, and taste and with the creation and appreciation of beauty. What if, aesthetics is processed in an artificial intelligence to help graphic designers and information technology (IT) in designing a website. This article is organized as an important introduction to both fields, namely visual communication design and information technology (IT). This research uses a qualitative method with a descriptive presentation to provide important data in applying what aesthetic considerations are present in artificial intelligence when designing user interfaces on websites.